Prospective validation of the RAPID clinical risk prediction score in adult patients with pleural infection: the PILOT study. Issue 5 (26th November 2020) - Corcoran, John P.; Psallidas, Ioannis; Gerry, Stephen; Piccolo, Francesco; Koegelenberg, Coenraad F.; Saba, Tarek; Daneshvar, Cyrus; Fairbairn, Ian; Heinink, Richard; West, Alex; Stanton, Andrew E.; Holme, Jayne; et al.
Background: Over 30% of adult patients with pleural infection either die and/or require surgery. There is no robust means of predicting at baseline presentation which patients will suffer a poor clinical outcome. A validated risk prediction score would allow early identification of high-risk patients, potentially directing more aggressive treatment thereafter. Objectives: To prospectively assess a previously described risk score (the RAPID (Renal (urea), Age, fluid Purulence, Infection source, Dietary (albumin)) score) in adults with pleural infection. Methods: Prospective observational cohort study that recruited patients undergoing treatment for pleural infection. RAPID score and risk category were calculated at baseline presentation. The primary outcome was mortality at 3 months; secondary outcomes were mortality at 12 months, length of hospital stay, need for thoracic surgery, failure of medical treatment and lung function at 3 months. Results: Mortality data were available in 542 out of 546 patients recruited (99.3%). Overall mortality was 10% at 3 months (54 out of 542) and 19% at 12 months (102 out of 542). The RAPID risk category predicted mortality at 3 months. Low-risk mortality (RAPID score 0–2): five out of 222 (2.3%, 95% CI 0.9 to 5.7%); medium-risk mortality (RAPID score 3–4): 21 out of 228 (9.2%, 95% CI 6.0 to 13.7%); and high-risk mortality (RAPID score 5–7): 27 out of 92 (29.3%, 95% CI 21.0 to 39.2%). C-statistics for the scores at 3 months and 12 months were 0.78 (95% CI 0.71–0.83) and 0.77 (95% CI 0.72–0.82), respectively. Conclusions: The RAPID score stratifies adults with pleural infection according to increasing risk of mortality and should inform future research directed at improving outcomes in this patient population. This multicentre observational study shows that RAPID score can stratify adults with pleural infection into categories according to increasing risk of 3-month mortality and should inform future research directed at improving outcomes in this population https://bit.ly/37tk2LN